Auto-Fluorescent Phytoliths: A New Method for Detecting Heating and Fire. (4th July 2021) - Devos, Yannick; Hodson, Martin J.; Vrydaghs, Luc
ABSTRACT: A range of methods have been applied to identify whether phytoliths have been heated or fired: morphological alterations, changes in colour and opacity, refractive index and Raman spectroscopy. As not all phytoliths seem to be affected in the same way, these methods are obviously limited and none provide satisfactory results for sufficient discrimination between heated/burned and unheated/unburned phytoliths. We surveyed phytoliths in soil thin sections taken from a variety of modern and archaeological contexts in Northern Europe. Newly formed phytoliths are argued to exhibit no auto-fluorescence. Our observations of combustion features and heated material revealed that phytoliths commonly appear to become auto-fluorescent upon heating. This approach, thus, complements previously developed proxies for heating and burning of phytoliths.